REPOSISI DAN EKSISTENSI MADRASAH SALAFIYAH DI ERA GLOBAL - Marwan Salahuddin (Cendekia: Kependidikan dan Kemasyarakatan, 2013)
Abstract: Madrasah is an educational institutions have developed varied , with the times . Most madrasah became public educational institutions distinctively Muslim ,most complete knowledge of religion taught in public schools because of the number of hours of very few studies , some still remain committed madrasah as an institution that  studies  the  Islamic  sciences  . Then  this madrasah  is referred  to  the Madrasah Salafiyyah . Generally, these types of madrasah teach Islamic sciences which writes by Ulama Salaf, so if it is associated with the development of science and technology in  this globalization era has missed most of  the material  , but  in  fact  this kind of madrasah still exist with a variety of activities . This can happen because the madrasah managers capable of adapting to changes in the global era . Old tradition that is still well maintained in order to fortify the negative influence of the various cultures that can undermine Islamic values   . Similarly, the maintenance of the values   as the basis for the formation of character with more emphasis on the primacy of worship and devotion to duty as a parent and teacher glorify ukhrawi approach continue to be preserved . Thus madrasah salafiyah will be more in demand , due to appear in the form of a new face, but the values    still follow the previous scholars. ضعب حبصأف ،نامزلا مدقت بكاوت اعونتم  – ةيملسإ ةيوبرت ةسسؤمك – ةينيدلا ةسردلا تن :صخلم ةيبيرجتلا مولعلاب ةينيدلا داولا تلمكأ رخلا ضعبلاو ،ةيملسإ ةزيب ةزيمتلا ةماع ةيوبرت ةسسؤم سرادلا نم ثلاثلا عونلاو .طقف ةيملسلا مولعلا سردت لازت ل تلا ةسردلا رخلا ضعبلاو ،ةليلق اهتصح ددع نل ءاملعلا فيلأت ةيملسلا بتكلا سردت – ةماع – ةسردلا هذه لثم نإ . ةيفلسلا ةسردلاب يمسلا وه ةسردلا ةمئاق  سرادلا  هذه نكل  ،ةرخأتم اهداوم ضعب  ناك ،ايجولونكتلاو مولعلا  مدقتب  نروق  ول  ىتح ،يفلاسلا ىلع ةسردلا تظفاحو ،ةلوعلا رصع ف تايغتلا عاونأب ةسردلا جمد ىلع رداق ةسردلا هذه مظنم نل ،ةتباث كولسلا نيوكتل ميقلا ىلع كلذك ظفاتو .ةماّ دلا تارّ ثؤلا نع ةيملسلا ميقلا ظافل ةلاصلا ةيدقلا ميقلا نوكتس ،اهلك هذهب .يورخلا لخدلاب يملعلاو نيدلاولا ماركإ بوجوو ةيدوبعلاك ةدابعلا حور لإ هاتلاب.لاصلا فلسلل ميقلا تعبتا اهنكل ديدج هجوب ترهظ اهنل ،بلطلا تابغر عضوم ةيفلسلا سرادلا هذه